Tool to assess appeal–aversion response to graphic warning labels on cigarette packs among US smokers. Issue 3 (28th April 2020) - Stone, Matthew D; Dimofte, Claudiu V; Strong, David R; Villasenor, Adriana; Pulvers, Kim; Messer, Karen; Pierce, John P
Abstract : Introduction: Graphic warning labels on cigarette packaging are mandated in 118 countries and are under consideration in the USA. We propose an appeal–aversion assessment tool to help regulators choose among graphic packaging options. Methods: After familiarisation with different cigarette packaging, adult daily smokers (n=338) from San Diego, California, USA completed a discrete choice appeal–aversion purchasing task and provided information on nicotine dependence and sociodemographics (2017–2019). The conjoint analysis estimated the importance and price utility for product attributes (ie, packaging, price, tobacco origin and quitline number). The price premiums that smokers would be willing to pay to avoid purchasing graphic packaging were calculated. Results: Among purchase determinants, the price was the most important attribute (65.5%), followed by packaging design (27.1%). Compared with blank packaging without marketing, branded industry packs had appeal valuations (US$0.54; 95% CI: US$0.44 to US$0.65), whereas graphic warning packs had aversion valuations that varied with the salience of the image (blindness=−US$2.53, 95% CI: −US$2.76 to −US$2.31; teeth damage=−US$2.90, 95% CI: −US$3.17 to −US$2.63; and gangrenous foot=−US$3.70, 95% CI: −US$4.01 to −US$3.39). The aversion was such that 46.2% of participants were willing to pay a 50+% premium over their current cigarette price to have their branded packs rather than a graphic pack. These appeal–aversion valuations were moderated by sex, income and nicotine dependence (p<0.05). Conclusions: Smokers indicated a willingness to pay substantial premiums to avoid purchasing graphic packaging. Results suggest that mandating graphic warnings on US cigarette packs would induce price aversion and may deter cigarette purchasing. Price valuations from this appeal–aversion tool could be useful for regulators to differentiate between graphic warning labels.